Collective Memory: Moral and Cultural Values on The Songs of Makalelon-Makaaruyen: Oral Tradition of Tontemboan Minahasa - Arter Jodi Senduk; Tatiana Stary Claudia; Buyung Ade Saputra (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
This article examines the oral tradition of Makalelon-Makaaruyen songs among the Tontemboan Minahasa people, a traditional sub-ethnic song form originating from the Minahasan community in Indonesia. Performed in Tontemboan, Manado Malay, and Indonesian, these songs serve as repositories of collective memory, preserving moral teachings and cultural values across generations. This study underscores the enduring role of these songs in upholding moral and cultural principles, collective memory, and cultural continuity, emphasizing the importance of oral tradition in sustaining identity and values among the Tontemboan Minahasa. Functioning as a medium of cultural transmission, the songs embody prayers, petitions, social virtues, and expressions of love for the homeland. Rooted in the Tontemboan sub-ethnic heritage, Makalelon-Makaaruyen songs encapsulate the community’s shared identity and historical consciousness, passed down orally through generations. The collective memory they preserve strengthens social bonds and mirrors the Minahasa people’s cultural worldview through Moral and Cultural Values conveyed, Sociocultural Context and Usage, and Social and Cultural Functions. This article demonstrates how these oral traditions serve as a living heritage that reinforces Minahasa cultural resilience as one among other collective memory of cultural expressions that heartedfully symbolizes and expresses, “Pakutuan Wo Pakalowiren/Pakalowiden”.